The Role of Green Business Strategy in Enhancing Digital Marketing Strategy for Sustainable Business Intelligence - Shwawreh, Sally; Awamleh, Fawwaz Tawfiq; Al Htibat, Ameen; Altarawneh, Abeer Sultan (International Review of Management and Marketing, 2025)
This study aims to analyze the role of green business strategy in enhancing digital marketing strategy towards SBI in SMEs operating in the digital marketing and technology sectors in Jordan. The total sample consisted of 33 SMEs, each with 417 administrative employees. All these proposed hypotheses were tested by Smart PLS 4. These results proved that the digital marketing strategy impacts SBI directly and indirectly via the green business strategy. Also, the green business strategy moderates the impact of the digital marketing strategy on SBI in aligning sustainability objectives with marketing efforts. Thus, this study provides practical implications for SMEs to develop integrated digital and green strategies for driving sustainability-driven intelligence frameworks.